Effect of glutathione supplementation during sperm preparation and in vitro fertilization on ovine embryo development - RANGASAMY, S; KULASEKAR, K; BALASUBRAMANIAN, S; RAJ, G DHINAKAR (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to investigate the effect of glutathione (GSH) supplementation during sperm preparation media (SPM) and in vitro fertilization (IVF) media on ovine embryo development. Six independent trials with a total of273 oocytes were carried out with GSH supplementation at 0.3 mg/ ml during SPM and IVF, 263 oocytes without supplementation formed the control. The mean cleavage rates were 48.46 ± 0. l 5 and 46.68 ± 0.12 per cent (P<0.0 I) in the treatment and control group, respectively. The percentage of morula (mean ± SE) that developed in treatment and control group were 24.58 ± 0.32 and 19.80 ± 0.24, respectively. The percentage of embryo that developed to the morula stage were significantly higher (P<0.0 l) in treatment group. GSH supplementation dijring SPM and IVF improved the cleavage and morula development.